EFFECT OF ZEIN ON CIPROFLOXACIN FLOATING TABLETS - SINGH, ANSHIKA; RAJORA, ANJALI; MAZUMDER, RUPA; PADHI, SWARUPANJALI (International Journal of Applied Pharmaceutics, 2022)
Objective: This work was aimed to formulate and evaluate the effect of zein on Ciprofloxacin HCl floating tablets. According to previous studies, it was set up to be useful against bacteria i.e. Helicobacter pylori which leads to peptic ulcers. Thus, it is quite necessary to enhance the Gastric Retention Time for similar medicines. Methods: 12 different floating tablets of Ciprofloxacin HCl were formulated with wet granulation method with a rise in the concentration of zein. Further, all different formulations prepared were evaluated for different parameters i.e. pre-compression considerations, along with post-compression factors like weight variation, content uniformity, thickness, visual assessment, hardness, friability, buoyancy studies i.e. total floating time as well as floating lag time, swelling index, dissolution and drug release kinetics. Results: The F6 formulation was considered to be among finest formulation with appropriate hardness. It was found that with the increasing concentration of zein, the hardness of tablets was also increased. It showed TFT of more than 7 h, FLT of 310 sec, a swelling index time of 99.5 % in 4 hr, while drug release kinetics was found to follow Higuchi Model. Conclusion: Overall it was also found that HPMCK-100M is more effective as compared to HPMC-K15M and Zein has a major role in increasing the hardness of tablets. In the future, the investigation will be continued with the following studies: An in vivo study and a long-term stability study.